Respuesta :
Solve: 12 - 2x = -2(y - x)
Steps:
1. Expand -2(y - x): -2y + 2x
12 - 2x = -2y + 2x
2. Then subtract 12 from both sides
12 - 12 - 2x = -2y + 2x - 12
3. Simplify,
-2x = -2y + 2x - 12
4. Then, subtract 2x from both sides
-2x - 2x = -2y + 2x - 2x - 12
5. Simplify,
-4x = -2y - 12
6. Then, divide both sides by -4
-4x/-4 = -2y/-4 - 12/-4
7. Simplify,
x = 1/2y + 3 <======= Answer
Hope this helped!!!!
The expression for x in terms of y is [tex]x=\frac{y+6}{2}[/tex]
Equations are expressions separated by an equal sign.
Given the equation
12-2x=-2(y-x)
We are to make x the subject of the formula
Expand the bracket using the distributive law:
[tex]12-2x=-2(y-x),\\12-2x=-2y+2x[/tex]
Collect the like terms
[tex]-2x-2x=-2y-12[/tex]
Divide through by 2
[tex]-x-x =-y-6\\-2x=-y-6\\2x=y+6[/tex]
Divide both sides of the expression by 2:
[tex]\frac{2x}{2} =\frac{y+6}{2}\\x= \frac{y+6}{2}\\[/tex]
Hence the expression for x in terms of y is [tex]x=\frac{y+6}{2}[/tex]
Learn more here: https://brainly.com/question/21406377